Tomography System Towards The Industrial Revolution 4.0 - Syarfa Najihah Raisin; Fatinah Mohd Rahalim; Yasmin Abdul Wahab; Ruzairi Abdul Rahim; Farah Aina Mohd Jamal; Nurul Arina Hazwani Samsu Zaini; Juliza Jamaludin; Fauzun Abdullah Asuhaimi; Wan Zakiah Wan Ismail; Irneza Ismail (Malaysian Society for Computed Tomography and Imaging Technology-MyCT, 2024)
Vol. 4 No. 2 (2021): Volume 4, Issue 2 (2021)